PROBLEMA ORGANISASI PROYEK PELAKSANA KONSTRUKSI BANGUNAN - Hanif Hanif (Portal: Jurnal Teknik Sipil, 2011)
The efforts to improve man power quality are the efforts that is done by contractor to improve its work quality. Improving the man power quality principally influences of internal and external factors. The objective of this study is to answer the internal factors that influences project team performance quality in organization structure of contractor project at building construction implementation and to determine the variables that are needed to improve contractor enterprise quality. This research used building construction project which have done in 2010 at Lhokseumawe city, collecting by disseminating Likert questionnaire. Respondents were chosen from contractor elements, those were project managers and field supervisors. This research used descriptive and inferential analysis. The results showed that the overlapping of job descriptions among division in project organization project, the ability to put workers in project, the ability of adaptation in any changes, the tools and machines condition that are used, and the time realization that appropriates to project schedule that is done, are the dominant sub aspects influenced project performance optimization. The influence of organization aspect, workers aspect, physical environment aspect, tools and technology that are used in project aspect, and team performance quality in contractor project organization aspect towards project performance optimization aspect was 69,6%.Keywords: project performance optimization, team performance quality